Quranic References in Sira Literature: A Prolegomenon to The Orientalist Studies - Ahmad Sanusi Azmi; Mohd Yusuf Ismail; Zulhilmi Mohamed Nor; Amiruddin Mohd Sobali; Amran Abdul Halim (Universiti Sains Islam Malaysia, 2024)
As early as eight century, critical analysis on the Qur’ān and Sīra has been conducted by various scholars. John of Damascus and other non-Muslim scholars were considered as among the earliest figures that manage to publish studies on this particular subject. The content of the Qurʾān and its relationship with the Sīra of the Prophet has stimulates historian to organise specific examination on Islamic literature including scrutinising the origin of Islam. At the outset of 19 century, various methods have been introduced and employed on the study of the Qurʾān and Sīra. Thus, this paper aims to (1) explore the critical analysis imposed by the orientalist on their study, (2) scrutinise their approaches and (3) analyse the relationship between the Qurʾān and narratives in Sīra according to Orientalist perspectives. This study is qualitative in nature in which researcher employed textual analysis as their main instrument. The study in its finding identifies three different methodologies, applied by the orientalist in their study on the Qurʾān and its relationship to the Sīra narratives